Madrid on the move : feeling modern and visually aware in the nineteenth century - Rodríguez-Galindo, Vanesa (Manchester : Manchester University Press, 2021)
Madrid on the move offers an account of illustrated print culture and the urban experience in nineteenth-century Spain. It provides a fresh account of modernity from a transnational perspective. Drawing on different kinds of printed images and texts, the book explores what being modern meant to people in their daily lives.
Includes bibliographical references and index.
Online resource; title from PDF title page (JSTOR, viewed May 21, 2021).
JSTOR
Keywords: Madrid (Spain) -- Civilization -- 19th century; Madrid (Spain) -- Social life and customs -- 19th century; Civilization, Modern -- 19th century; Illustrated periodicals -- Spain -- Madrid -- History -- 19th century; Civilisation -- 19e siècle.; Magazines (Publications) -- Espagne -- Madrid -- Histoire -- 19e siècle.; Civilization; Civilization, Modern; Illustrated periodicals; Manners and customs; Spain -- Madrid; 1800-1899; Electronic books; History